2016
DOI: 10.1530/joe-15-0463
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon receptor antagonist and GIP agonist combination for diet-induced obese mice

Abstract: Ablation of glucagon receptor signaling represents a potential treatment option for type 2 diabetes (T2DM). Additionally, activation of glucose-dependent insulinotropic polypeptide (GIP) receptor signaling also holds therapeutic promise for T2DM. Therefore, this study examined both independent and combined metabolic actions of desHis 1 Pro 4 Glu 9 (Lys 12 PAL)-glucagon (glucagon receptor antagonist) and d-Ala 2 GIP (GIP receptor agonist) in diet-induced obese mice. Glucagon receptor binding has been linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…However, we have recently shown that combined administration of a peptidic GCGR antagonist, with the well-characterised GLP-1 receptor mimetic exendin-4, exerts limited additive metabolic benefits ( Franklin et al 2022 ). Thus, activation of receptors for the sister incretin hormone of GLP-1, namely glucose-dependent insulinotropic polypeptide, may offer a more attractive paradigm in terms of combination therapy with GCGR antagonism ( McShane et al 2016 ). However, intestinal L-cell number has also been demonstrated to be reduced by STZ administration ( Vasu et al 2015 ), which could represent another confounding factor in our current observations.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have recently shown that combined administration of a peptidic GCGR antagonist, with the well-characterised GLP-1 receptor mimetic exendin-4, exerts limited additive metabolic benefits ( Franklin et al 2022 ). Thus, activation of receptors for the sister incretin hormone of GLP-1, namely glucose-dependent insulinotropic polypeptide, may offer a more attractive paradigm in terms of combination therapy with GCGR antagonism ( McShane et al 2016 ). However, intestinal L-cell number has also been demonstrated to be reduced by STZ administration ( Vasu et al 2015 ), which could represent another confounding factor in our current observations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, xenin-6, but not Ψ-xenin-6, had a strong tendency to reverse GIP-mediated increases in glucagon release. This is interesting, as both augmentation and blockade of glucagon receptor signalling has been advocated as being beneficial in diabetes (Pathak et al, 2015;McShane et al, 2016). The difference in biological activity between the two xenin C-terminal hexapeptides is intriguing and presumably not related to the enhanced stability of Ψ-xenin-6 noted here and elsewhere (Feurle et al, 2002).…”
Section: Previous Reports Have Established That Chemical Manipulationmentioning
confidence: 67%
“…Glucagon receptor knockout mice display reduced glycemia in response to exogenous insulin (Gelling et al, 2003) and require greater amounts of glucose to maintain euglycemia during hyperinsulinemiceuglycemic clamp experiments (Longuet et al, 2013;Sørensen et al, 2006). These improvements in peripheral insulin sensitivity have also been reported in mice where glucagon receptor signaling has been pharmacologically inhibited (McShane et al, 2016;Sharma et al, 2018). When liver-specific glucagon receptor knockout models are employed, insulin sensitivity is increased to a level comparable to global knockouts (Longuet et al, 2013), indicating that hepatic glucagon receptor signaling is the primary mediator for these benefits.…”
Section: Discussionmentioning
confidence: 95%